2008
DOI: 10.1111/j.1467-9701.2008.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Free Trade Agreements and Customs Unions: The Impact of the EU Republic of South Africa Free Trade Agreement on Botswana

Abstract: The EU has indicated that after 2008 its trade relationships with developing countries will be dominated by the development of preferential trade agreements. Although not a consequence of the Cotonou Agreement, the free trade agreement between the EU and the Republic of South Africa (EU RSA FTA) is clearly one of the first fruits of this approach to trade relationships. However, there is no evidence that the design of the EU RSA FTA incorporated a comprehensive general equilibrium evaluation of the agreement f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…We used the standard GTAP model with a few adjustments in the closure rules to accommodate different scenarios used in the simulations. As in McDonald and Walmsley (2003), we include three fundamental adjustments to the standard GTAP closure. First, we adopt a fixed trade balance to account for the fact that developing and underdeveloped countries follow a managed float regime.…”
Section: Model and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…We used the standard GTAP model with a few adjustments in the closure rules to accommodate different scenarios used in the simulations. As in McDonald and Walmsley (2003), we include three fundamental adjustments to the standard GTAP closure. First, we adopt a fixed trade balance to account for the fact that developing and underdeveloped countries follow a managed float regime.…”
Section: Model and Datamentioning
confidence: 99%
“…The sector breakdown consisted of 15 sectors that were aggregated from the 57-sector GTAP database (see Table A.3). The regional and commodity aggregations reflected the known patterns of trade and various trade agreements in Central Africa (McDonald and Walmsley, 2003). For country-specific analysis, the DR Congo and Cameroon are analysed separately from CEMAC.…”
Section: Model and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Commodities in this study were grouped into nine sectors in accordance with characteristics and types, includes Agricultural Products, Food Products, Extractive Industry, Textiles, Heavy Manufacturing, Technology-intensive Manufacturing, Utilities, Construction and Services. Agglutination of the commodities traded in this study refer to Park et al (2008);and McDonald and Walmsley (2003); and are adapted to the purpose of research.…”
Section: Simulation Designmentioning
confidence: 99%
“…Most economists argue that free trade has a positive impact, Estrada, et al (2011) argue that an ASEAN-China-Japan-Korea (ASEAN + 3) agreement would provide positive welfare and GDP for the entire region; AFTA (ASEAN free trade area) going to be trade creation and investment (Pardo et al, 2009), (Bowles, 1997)]; the Japan and Singapore FTA causes a wider access and strengthens trade flows, and then enhances the trade in goods and investments (Hertel et al, 2001); FTAs will have an positive impact on welfare, trade, and the trade balance surplus (Gilbert, 1998); the Bilateral FTA between Australia and China creates a strong trade relationship that is complementary in nature, thus forming a trade specialisation pattern that leads to a comparative advantage (Siriwardhana and Yang, 2007); the UE-15 and CEEC-4 free trade agreement has a determinate and significant impact on trade flow among member countries (Caporale et al, 2009). While the negative impact of the FTA among others, Yeats (1998) argues that the MERCOSUR (Brazil, Argentina, Paraguay, and Uruguay free trade agreement) does not provide a comparative advantage for all countries, caused trade diversion and reduce on welfare; McDonald and Walmsley (2003) found that the EU-RSA FTA (European Union and Republic of South Africa free trade agreement) negatively impacts on South Africa and the adjacent countries; Trefler (2004) concluded that Canada-USA free trade agreement led to employment loses up to 12 percent for Canada; Horagochi (2007) note that FTA cause systemic turbulence and trade diversion in the regional economies; trade diverted on large intra-industry will have negative impact on welfare, while trade diverted on intra-industry hard to explain (Cheong and Wong, 2007 The purpose of this research is to simulate the impact of free trade cooperation between ASEAN and Korea (AKFTA) and between ASEAN and India (AIFTA). This study implements the Computable General Equilibrium (CGE) model using the Global Trade Analysis Project (GTAP) database 8 approach for quantitative assessment of these cooperation.…”
Section: Introductionmentioning
confidence: 99%